Prognostic value of elevated high-sensitivity cardiac troponin T in patients admitted to an emergency department with atrial fibrillation - Stoyanov, Kiril M.; Giannitsis, Evangelos; Biener, Moritz; Müller-Hennessen, Matthias; Arens, Katharina; Katus, Hugo; Vafaie, Mehrshad (Europace, 2018)
AimsElevated levels of high-sensitivity cardiac troponin T (hsTnT) indicate underlying heart disease and are known to predict adverse outcomes in various patient populations. Their role in atrial fibrillation (AF) is still under debate.Methods and resultsThis retrospective study included 2898 consecutive patients presenting with AF to the emergency department of the Department of Cardiology, Heidelberg University Hospital. Multivariable Cox regression was used to assess associations between hsTnT and mortality. Elevated hsTnT levels were associated with increased risk of all-cause mortality in all patients with AF, as well as in each subtype of AF. After adjustment for multiple risk factors, both detectable hsTnT below the 99th percentile (5-14 ng/L, adjusted hazard ratio (HR): 4.86 [95% CI: 1.77-13.34], P = 0.002) and elevated hsTnT (>14 ng/L, adjusted HR: 13.42 [95% CI: 4.95-36.40], P < 0.001) were associated with a higher risk of mortality in patients with AF, compared to undetectable hsTnT (<5 ng/L). Elevated hsTnT was also associated with higher mortality after exclusion of patients with myocardial infarction, as well as in the subgroup of patients with AF as main admission diagnosis. The inclusion of hsTnT significantly improved the performance of the multivariable model for mortality prediction.ConclusionElevated hsTnT levels are associated with higher mortality in patients with AF, and provide added prognostic information independent of major cardiovascular risk factors and clinical characteristics. Measurement of hsTnT should be considered for risk assessment in patients presenting to an emergency department with AF.Clinical trial registrationhttp://www.clinicaltrials.gov; Unique identifier: NCT02542189.